Permanent Sovereignty over Natural Resources
XVI, 221 p.
Keywords: Fifty years after the adoption of the Declaration on Permanent Sovereignty over Natural Resources by the General Assembly of the United Nations in December 1962, this volume assesses the evolution of the principle of permanent sovereignty over natural resources into a principle of customary international law as well as related developments. International environmental and human rights law leave unresolved questions regarding the limitations of this principle, e.g. extraterritorial and international influences such as the applicable criminal and tort law, as well as the extraterritorial and international promotion of good governance, including transparency obligations.